Sources of Errors in the Evaluation of Performance Employees in the Sector of Public Administration Reform in Bosnia and Herzegovina - Adisa Delic; Mirela Cebic (Economic Review: Journal of Economics and Business, 2011)
This paper is focused on the process of evaluating performance of employees. Special emphasis has been put on possible errors that may impair the objectivity of the outcome of this process. The purpose of implementing this process lies in identifying potential employees, providing information that can serve as a basis for human resource planning, forming a basis for assessing the effectiveness of the process of professional selection, establishing training needs and planning employees' training, reinforcing the motivation of employees at work, etc. However, due to inadequate structure of the system of performance evaluation, there appears to be a list of various errors that limit their objectivity. Hence, the purpose of this study is to indicate the possible sources of errors and mistakes in evaluating the performance, with special emphasis put on empirical research conducted in this field in the sector of public administration of Bosnia and Herzegovina (B&H).
Keywords: M5; 330; errors in the evaluation of performance; sector of public administration; Bosnia and Herzegovina